Analisis Keunggulan Kompetitif PT. Galenium Pharmasia Laboratories - , Cis Antono, Dr. Fahmy Radhi, MBA ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The purpose of this research is to evaluate and analyze the relevance of competitive strategy applied by the company to achieve sustainable competitive advantage in facing industrial competition. The industrial sector evaluated is PT Galenium Pharmasia Laboratories, a company that manufacture drugs and consumer goods. This research use qualitative analytical method. To evaluate competitive advantage, first is generic competitive strategy analysis, then industrial analysis to examine which external factors that influence the company generally. Then, SWOT analysis is done to examine strength, weakness opportunities and threats that the company is dealing. After each factor that influence the company is identified, then a strategy to achieve sustainable competitive advantage can be formulated. The company business strategy is best-cost and differentiation. From the research, can be concluded that Galenium Pharmasia Laboratories competitive strategy needs to be improved to face the pharmaceutical industry and consumer goods competition